2022
DOI: 10.1590/1413-81232022273.45982020
|View full text |Cite
|
Sign up to set email alerts
|

Tendência temporal da leptospirose e sua associação com variáveis climáticas e ambientais em Santa Catarina, Brasil

Abstract: Resumo A leptospirose é uma zoonose que apresenta potencial epidêmico, principalmente após fortes chuvas que acarretam inundações, alagamentos e enxurradas. Algumas características da região costeira de Santa Catarina, localizada no Sul do Brasil, influenciam nesses processos. Portanto, a partir do estudo da leptospirose nos seis municípios do estado com as maiores incidências e picos epidêmicos de 2000 a 2015, buscou-se conhecer a tendência dessa doença e as variáveis climáticas e ambientais associadas à sua … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Minimum temperature, lagged by one week, was also found to be positively associated with leptospirosis risk. Several studies have previously identified that temperature may have a role in leptospirosis outbreaks [47][48][49][50][51], although this appears to be context specific, as other studies have not…”
Section: Discussionmentioning
confidence: 89%
“…Minimum temperature, lagged by one week, was also found to be positively associated with leptospirosis risk. Several studies have previously identified that temperature may have a role in leptospirosis outbreaks [47][48][49][50][51], although this appears to be context specific, as other studies have not…”
Section: Discussionmentioning
confidence: 89%
“…Além disso, é preciso melhorar o saneamento e ter medidas emergenciais já planejadas no caso de ocorrências de enchentes e desastres naturais. É fundamental também que os profissionais de saúde estejam aptos e preparados para lidar adequadamente com a investigação acerca da doença e de possíveis intervenções a pacientes que necessitem de diagnóstico e tratamento, se positivado (Silva et al, 2022).…”
Section: Resultsunclassified
“…Outdoor recreational activities, including rafting, triathlons, canoeing, or bathing in contaminated natural water reservoirs are well-known risk factors in developed countries [16 ▪▪ ]. Epidemic outbreaks have been reported all over the world following floods [7 ▪ ,16 ▪▪ ,17].…”
Section: Pathogen and Mode Of Transmissionmentioning
confidence: 99%
“…carried by rats traded remains limited [36]. Brazil, identified L. copenhageni in human leptospirosis, animals, and environmental reservoirs [7 ▪ ,12,37]. Human leptospirosis has been reported from several other countries, including Vietnam and China [38,39].…”
Section: Current Trend-epidemiologymentioning
confidence: 99%
See 1 more Smart Citation